Recreational night life. Can it give rise to violent behaviours? - Lomba, Maria de Lurdes Lopes de Freitas (2013)
Introduction: Night recreational settings have become a key location for the socialization of young people. However the hedonistic culture promoted the consumption of alcohol and drugs that for some young people health risk behaviours such as alcohol and drug use and violence are necessary conditions to have fun in night recreational places Aim: to determine the prevalence of violent behavior associated with alcohol and drug consumption and participation in recreational nightlife activities of Portuguese young people. Design: Quantitative, descriptive-correlational study. Sample: 1346 clubbers of both sexes with a mean age of 22.49 years selected by Respondent-driven Sampling across 10 Portuguese cities at nightlife leisure settings. Results: young people have regular habits of going out at night, especially on weekends. The most used substances are alcohol, cannabis, cocaine and ecstasy. Last year, in nightlife venues, 2.76% carried weapons, 8.55% were threatened/injured with a weapon and 8.17% were involved in fights. There's a positive correlation between how often they were in fights or were threatened/injured and alcohol and drug's consumption, and with their engagement in recreational activities. Males and young people with lower education most often adopt the studied violent behaviors. Young people from a lower socioeconomic status carry weapons more often than those of an upper-middle status, but these latter get involved in fights more often or are threatened/injured more often. Younger people are the ones who fight most often. Conclusions: the influence of psychoactive substances and other risky determining factors should be taken into account on young people behavior who attends night recreational settings. Results from this study point towards the need for harm reduction programs which consider recreational settings as an environmental factor for violence and alcohol and drug use and also specific measures addressed to young people as the suggested "motivational interview" to reduce personal risk behaviours.